Intellectual Property Rights in the Digital Era: Exploring the Legal Aspects of Copyright in the Context of Digital Content Sharing and Online Platform - Ajabe-Alhat, Rahi; Priyadarshi, Divyanshu; Chaudhery, Urvesh; Ramchandran, Sharmila Devi (Journal of Ecohumanism, 2024)
Protecting and enforcing intellectual property rights have become increasingly complex and challenging in the digital era. This article discusses the legal aspects of intellectual property, with a particular focus on copyright within the context of the digital era. It explores the evolving nature of intellectual property laws and discusses the importance of comprehensive legal frameworks that need to focus on the unique challenges posed by the digital age. One of the critical areas of concern is copyright protection in digital content-sharing. The rise of online platforms and digital technologies has revolutionised content creation and dissemination and has given rise to significant copyright infringement issues. This article examines the copyright challenges that creators, right holders, and digital platforms face and explores the legal mechanisms to combat copyright infringement in the digital realm. By shedding light on these topics, this article aims to contribute to a better understanding of copyright under intellectual property rights in the dynamic and rapidly evolving digital ecosystem. It emphasises the need for strong legal frameworks that balance protecting intellectual property and promoting creativity in the digital age.